Abordagem metalômica quantitativa de mercúrio em peixes da região amazônica - Queiroz, João Vitor de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents the results of mercury fractionation in muscle samples of tucunaré (Cichla spp.) and filhote (Brachyplatystoma filamentosum) from the JIRAU Hydroelectric Power Plant in the Madeira River Basin in the Amazon region of Brazil. The proteome of the fishes muscle was separated by two-dimensional polyacrylamide gel electrophoresis (2D PAGE). The mercury present in the protein spots was determined by graphite furnace atomic absorption spectrometry (GFAAS) after acid mineralization in an ultrasound bath. The protein spots in which the presence of mercury was detected were characterised by electrospray ionisation tandem mass spectrometry (ESI-MS/MS) after tryptic digestion. The GFAAS determinations indicated that 65% of the mercury was linked to the protein fraction with a molar mass (Mm) of less than 90 kDa. The mercury concentration in the eleven spots in this protein fraction was present were in the range 13.60 to 17.10 mg g-1. Based on mercury concentrations, it was possible to estimate that the protein spots contained approximately one atom of mercury per protein molecule. Analysis by ESI-MS / MS protein allowed the characterization of ten spots as proteins and / or following enzymes: parvalbumin-2 (MW = 12.40, pI = 3.80); parvalbumin alpha (Mm = 12.40, pI = 3.80); parvalbumin beta (Mm = 12.40, pI = 3.80); ubiquitin-40S ribosomal protein S27a (Mm = 11.60, pI = 6.10); GTP cyclohydrolase 1 regulatory protein of feedback (Mm = 13.00, pI = 4.00) and transmembrane protein 186 (Mm = 14.00, pI = 4.70).

Este trabalho apresenta os resultados de fracionamento de proteínas ligadas ao mercúrio em amostras de músculo de tucunaré (Cichla spp.) e filhote (Brachyplatystoma filamentosum) oriundos do complexo hidrelétrico de Jirau, na Bacia do Rio Madeira, região amazônica do Brasil. O proteoma do músculo dessas espécies foi separado por eletroforese bidimensional em gel de poliacrilamida (PAGE 2D). O mercúrio presente nos spots proteicos foi determinado por espectrometria de absorção atômica em forno de grafite (GFAAS) após mineralização ácida assistida por banho de ultra-som. Os spots proteicos que apresentaram mercúrio foram caracterizados por espectrometria de massas por ionização com eletrospray em sequência (ESI- MS/MS) após digestão tríptica. As determinações GFAAS indicaram que 65% do mercúrio está ligada à fração proteica com massa molar (Mm) inferior a 90 kDa. As concentrações de mercúrio nos spots apresentaram-se na faixa de 13,60 – 17,10 mg g-1. Com base nas concentrações de mercúrio, foi possível estimar que os spots proteicos continham aproximadamente um átomo de mercúrio por molécula de proteína. A análise por ESI-MS / MS permitiu caracterizar em dez spots proteicos as seguintes proteínas e/ou enzimas: parvalbumina-2 (Mm = 12,40, pI = 3,80); parvalbumina alfa (Mm = 12,40, pI = 3,80); parvalbumina beta (Mm = 12,40, pI = 3,80); ubiquitina-40S proteína ribossômica S27a (Mm = 11,60, pI = 6,10); GTP cyclohydrolase 1 proteína reguladora de feedback (Mm = 13,00, pI = 4,00) e proteína de transmembrana 186 (Mm = 14,00, pI = 4,70).
Keywords: Peixe - Pesquisa; Metaloproteinas; Mercurio; Proteômica; Fishes; Amazônia - Aspectos ambientais